Право з погляду філософа - Попович, М.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2003)
Такие общечеловеческие ценности, как свобода, справедливость, солидарность являются одновременно и правовыми ценностями, включенными в конституции государств и соответствующие законодательные акты. В то же время выраженные в них юридические формулы объективно ставят сложную философско-правовую проблему их адекватности реальной справедливости или, возможно, наоборот, экспликации скрытого в них антигуманного смысла. Such common to the mankind human values as freedom, justice, and solidarity are simultaneously legal values, which are included provided in states’ constitutions and corresponding legislative acts. The legal
formulas expressed therein pose a complex philosophical and legal problem of their adequacy to actual justice
or, perhaps, to the contrary, the explication of anti-humane essence hidden in them.